1999
DOI: 10.1103/physrevb.60.13245
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of Si and Ge gold-doped clathrates

Abstract: The electronic properties of single phase type-I clathrate compounds, Ba 8 Au 6 (Si or Ge) 40 and Ba 8 Ge 46Ϫx have been investigated. The crystal structure, electrical resistivities, magnetic susceptibilities, the density of states at the Fermi level, and the band gap ͑where applicable͒ were determined. Ba 8 Au 6 Si 40 and Ba 8 Au 6 Ge 40 show a metallic behavior whereas Ba 8 Ge 46Ϫx is semiconducting. On a basis of this work, a first evidence is presented of the existence of type-I mixed-clathrates containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 12 publications
1
62
1
3
Order By: Relevance
“…The framework defects in K 8 Ge 44 £ 2 have been confirmed in recent works from powder diffraction data [12,13]. Moreover, the validity of the split atom model has been proven by the detection of superstructures with ordered defect arrangement (space group Ia3d )for the clathrate-I phases Rb 8Sn44£2 [14], Cs8Sn44£2 [15] and Ba 8Ge43£3 [9,16,17]. Interestingly, vacancies occur for the larger tetrel elemenst but not for the corresponding silicide.…”
Section: Discussionmentioning
confidence: 50%
“…The framework defects in K 8 Ge 44 £ 2 have been confirmed in recent works from powder diffraction data [12,13]. Moreover, the validity of the split atom model has been proven by the detection of superstructures with ordered defect arrangement (space group Ia3d )for the clathrate-I phases Rb 8Sn44£2 [14], Cs8Sn44£2 [15] and Ba 8Ge43£3 [9,16,17]. Interestingly, vacancies occur for the larger tetrel elemenst but not for the corresponding silicide.…”
Section: Discussionmentioning
confidence: 50%
“…Experimentally, it was found that the compound shows semiconducting behavior. 5,6 The apparent discrepancy from the simple valence rules has been tentatively ascribed to an ordering of the framework vacancies resulting in modifications of the electronic band structure near the Fermi level. 5 On the other hand, investigations on the ternary system Ba 8Àx Eu x Ge 43 (x < 0.6) revealed metallic behavior for the whole homogeneity range.…”
Section: Introductionmentioning
confidence: 99%
“…In Ba 8 46 exhibits an unbroken framework, as established through crystallography and NMR [27,62]. However its analog Ba 8 Ge 46 does not form a fully populated framework, instead favoring spontaneous vacancy formation [63,64], with the configuration Ba 8 Ge 43 3 , denoting the vacancies, with a superstructure as shown in Figure 11. According to a Zintl picture four vacancies, with 4 electrons each, might be expected to accept the 16 electrons from Ba 2+ , completing a network of filled bonds.…”
Section: Zintl Concept and Vacanciesmentioning
confidence: 93%